Antecedents and effects of individual absorptive capacity: a micro-foundational perspective on open innovation. Issue 6 (9th October 2017) - Lowik, Sandor; Kraaijenbrink, Jeroen; Groen, Aard J.
Abstract : Purpose: The paper aims to understand how individuals differ in individual absorptive capacity – their ability to recognize, assimilate, transform and exploit external knowledge. These individual absorptive capacities are a key knowledge management building block for an organization's open innovation practices. The study examines individual antecedents – human capital, social capital and cognition – and innovation outcomes of individual absorptive capacity. Design/methodology/approach: This is a quantitative study of 147 employees in a single medium-sized Dutch industrial firm. Based on a survey and structural equation modeling, the antecedents' prior knowledge diversity, network diversity and cognitive style are examined in relation to individual absorptive capacity. Further, the mediating effects of individual absorptive capacity on its antecedents and innovation outcome are investigated. Findings: The main findings are that prior knowledge diversity, external network diversity and a bisociative cognitive style explain differences in individual absorptive capacity. A bisociative cognitive style appears to be the most important factor. Also, this study finds that individual absorptive capacity mediates between its antecedents and individual innovation performance and is therefore a relevant factor to capture value from external knowledge sources. Research limitations/implications: The study extends open innovation theory by exploring individual-level factors that explain the ability to capture value from external knowledge. It suggests that differences in open innovation practices are explained by heterogeneity at the individual level. Further, it explains how individuals' potentials for open innovation are mediated by their absorptive capacities. These insights enable future researchers to further examine individual-level factors in knowledge management practices and to explore cross-level individual-organizational interactions for open innovation. Practical implications: This paper highlights that individuals' engagements in open innovation practices are explained not only by individuals' motivations but also by their abilities to absorb external knowledge. Further, it helps managers to design knowledge management practices to promote employees' absorptive capacities, to improve open innovation processes. Originality/value: This study investigates the neglected individual-level factors of open innovation practices from a micro-foundational and knowledge management perspective. To our best knowledge, this is the first study to examine individual-level antecedents and outcomes of individual absorptive capacity.